Checklist of Flora of Myristica Swamps - A Critically Endangered Fresh Water Ecosystem of Southern Western Ghats of Kerala, India - Roby, T. J.; Jose, Joyce; Vijayakumaran Nair, P. (Indian Forester, 2014)
Trees of Myristicaceae family are dominant hence these swamps are popularly known as ’Myristica’ swamps. Members of other families such as Celestraceae, Diptereocarpaceae, Anacardiaceae, Xanthophyllaceae, Myrtaceae, etc. are a significant part of the swamp community in some of these swamps, but are less frequent. Ground vegetation consists mainly of Pandanus, Calamus, Ochalandra and members of Araceae, Acanthaceae, and Zingiberaceae family. Endemic and Endangered species such as Myristica fatua var.magnifica, Syzygium trvancoricum, Vateria indica are well represented. Sixty swamps in Southern Kerala were surveyed and mapped recently. A check list of the plant species of Myristica swamp forests of southern Kerala, India from over a period of five years is presented. 221 species of plants belonging to 88 families have been recorded from these swamp forests. Of the total plant species in Kerala, 5% have been recorded from the Myristica swamp forests of Kerala, the cumulative area of which is less than 0.01% of the land area of the State. 79 species of trees, 93 species of herbs/shrubs and 49 climbers constitute the vegetation. Eighteen of these plants are in the redlist and 49 plants are endemic.